CD200/CD200R paired potent inhibitory molecules regulating immune and inflammatory responses; Part I: CD200/CD200R structure, activation, and function - Holmannová, Drahomíra; Kolácková, Martina; Kondélková, Katerina; Kunes, Pavel; Krejsek, Jan; Andrýs, Ctirad (Acta medica (Hradec Kralove), 2012)
CD200/CD200R are highly conserved type I paired membrane glycoproteins that belong to the Ig superfamily containing a two immunoglobulin-like domain (V, C). CD200 is broadly distributed in a variety of cell types, whereas CD200R is primarily expressed in myeloid and lymphoid cells. They fulfill multiple functions in regulating inflammation. The interaction between CD200/CD200R results in activation of the intracellular inhibitory pathway with RasGAP recruitment and thus contributes to effector cell inhibition. It was confirmed that the CD200R activation stimulates the differentiation ofT cells to the Treg subset, upregulates indoleamine 2,3-dioxygenase activity, modulates cytokine environment from a Thl to a Th2 pattern, and facilitates an antiinflammatory IL-10 and TGF-beta synthesis. CD200/CD200R are required for maintaining self-tolerance. Many studies have demonstrated the importance of CD200 in controlling autoimmunity, inflammation, the development and spread of cancer, hypersensitivity, and spontaneous fetal loss.
Keywords: Antigens, Surface; Antigens, CD; Receptors, Cell Surface; CD antigeny; zánět; Immunity; signální transdukce; Orexin Receptors; imunita; orexinové receptory; lidé; Animals; Inflammation; antigeny povrchové; receptory buněčného povrchu; zvířata; Humans; Signal Transduction